Building a Foundation for the Care of Children with Cancer in Rural North India - Nagabushan, Sumanth; Rao, Prashanth J.; Ganta, Roopa; Chaturvedi, Shailja (Indian Journal of Medical and Paediatric Oncology, 2022)
One of India's biggest challenges is to improve its global standing by increasing healthcare access and outcomes for children with cancer, with inferior overall survivorship compared with its Western counterparts. In conjunction with the government's efforts, private enterprise is crucial in delivering optimal cancer care consistently to its vast and diverse pediatric population, despite existing limitations. This article describes the successful implementation of a value-based, collaborative clinical and research framework by a philanthropic foundation in a rural Northern Indian city to establish and run a local childhood cancer service. It is proof of concept that substantial change could be brought about at grass roots level through resourceful partnerships and reduce prevailing imbalance in pediatric oncology service provision.
Keywords: India; pediatric oncology; charitable foundation; childhood cancer